2022
DOI: 10.3389/fped.2021.790109
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Hypoxic Community-Acquired Pneumonia in Children Under 5 Years of Age: An Observational Study in Northern India

Abstract: BackgroundCommunity-acquired pneumonia (CAP) is the leading cause of under-five mortality in India. An increased risk of mortality has been reported in cases of hypoxic pneumonia.MethodsThe primary objective of this study was to assess the proportion of children aged 2–59 months, hospitalized with hypoxic CAP, as well as socio-demographic, clinical, and radiological features associated with it. The secondary objective was to determine the risk of mortality among hospitalized cases of hypoxic CAP. This prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…They recommended using oxygen saturation and objective data to determine the severity of pneumonia (24). The study by Awasthi et al (28) emphasised that hypoxia and pneumonia in children under five years of age increase the mortality rate and may cause severe pneumonia. In their research, Modi et al (29) emphasised that the sensitivity of the oxygen saturation measurement in evaluating pneumonia is more predictive than other clinical findings in resourceconstrained conditions.…”
Section: Discussionmentioning
confidence: 99%
“…They recommended using oxygen saturation and objective data to determine the severity of pneumonia (24). The study by Awasthi et al (28) emphasised that hypoxia and pneumonia in children under five years of age increase the mortality rate and may cause severe pneumonia. In their research, Modi et al (29) emphasised that the sensitivity of the oxygen saturation measurement in evaluating pneumonia is more predictive than other clinical findings in resourceconstrained conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Malnutrition status were categorized as WAZ >-2SD (normal), WAZ ≤ -2SD (malnourished) and WAZ ≤ -3SD (severe malnutrition) [ 17 ]. Hypoxia was defined as oxygen saturation<90% on pulse oximetry or requiring oxygen supplementation during hospital stay [ 18 , 19 ]. Since respiratory syncytial virus (RSV) tends to peak in India in five months of early winter (June to October) and three months of winter (December to February), therefore these eight months were considered as RSV season [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Hypoxia is an important determinant of mortality and needs to be identified early and managed on priority. A recent study done by Awasthi et al reported 35.9% of 7196 under-five children hospitalised with WHO defined severe pneumonia had hypoxia among those unvaccinated with PCV13 [ 41 ]. Oxygen saturation <90% on pulse oximetry or requiring oxygen therapy during hospital stay was considered as hypoxic.…”
Section: Managementmentioning
confidence: 99%